2021
DOI: 10.3920/wmj2020.2669
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and concentration of mycotoxins in maize dried distillers’ grains produced in Brazil

Abstract: The presence of mycotoxins in dried distillers’ grains with solubles (DDGS), a by-product of bioethanol production from maize, has been a matter of concern due to the increasing global utilisation of this ingredient in animal feed. In this study, 186 samples of maize DDGS produced in Brazil were analysed for the presence of major mycotoxins: aflatoxins (B1, B2, G1, and G2), fumonisins (B1 and B2), zearalenone (ZEN), deoxynivalenol (DON) and ochratoxin A (OTA). Samples were provided by the local industry betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The authors registered 34.7% positivity for ZEN (average: 167.6 μg kg −1 ), whereas DON (average: 3000 μg kg −1 ) and FBs (average: 1010 μg kg −1 ) were detected in 28.7% and 25.3% of the samples, respectively. Mallmann et al 55 also used HPLC for determination of mycotoxins in 186 samples of corn DDGS originating from Brazilian ethanol plants and feed mills. The assessment disclosed that more than 98% of the samples were contaminated with at least one mycotoxin, with FB 1 and FB 2 being the most prevalent: 98.8% and 97.6% of the analyzed samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors registered 34.7% positivity for ZEN (average: 167.6 μg kg −1 ), whereas DON (average: 3000 μg kg −1 ) and FBs (average: 1010 μg kg −1 ) were detected in 28.7% and 25.3% of the samples, respectively. Mallmann et al 55 also used HPLC for determination of mycotoxins in 186 samples of corn DDGS originating from Brazilian ethanol plants and feed mills. The assessment disclosed that more than 98% of the samples were contaminated with at least one mycotoxin, with FB 1 and FB 2 being the most prevalent: 98.8% and 97.6% of the analyzed samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors registered 34.7% positivity for ZEN (average: 167.6 μg kg −1 ), whereas DON (average: 3000 μg kg −1 ) and FBs (average: 1010 μg kg −1 ) were detected in 28.7% and 25.3% of the samples, respectively. Mallmann et al 55 . also used HPLC for determination of mycotoxins in 186 samples of corn DDGS originating from Brazilian ethanol plants and feed mills.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mycotoxins in by-products of bioethanol industry, such as DDGS, is of concern due to their use as ingredients in animal feed. Mallmann et al (2021) surveyed DDGS samples produced in Brazil for aflatoxins, fumonisins, ZEN, DON and OTA. The study showed that about 99% of the samples were contaminated, 59.9% of which were contaminated with a single mycotoxin, 29.9% with two mycotoxins and 9.1% more than two mycotoxins.…”
Section: Occurrence Of Mycotoxinsmentioning
confidence: 99%
“…During the production of bioethanol from maize, mycotoxins are practically not degraded and/or eliminated. Even more, several studies have demonstrated that mycotoxins are not present in the produced bioethanol but are three times more concentrated in DDGS [ 12 , 18 , 19 , 20 , 21 , 22 ]. Additionally, it has been shown that mycotoxins can affect the behaviour of the yeast used during fermentation, decreasing bioethanol yields [ 3 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study carried out on 52 samples from the USA and European countries, Oplatowska-Stachowiak et al [ 29 ] detected up to 16 ng/g of AFB 1 in 75% of the DDGS samples. Recently, contamination levels of around 1.47 ng/g of AFB 1 were detected in 60 out of 186 DDGS samples in Brazil [ 21 ]. In general, AF contamination levels are relatively low.…”
Section: Introductionmentioning
confidence: 99%